2021
DOI: 10.1186/s12904-021-00864-6
|View full text |Cite
|
Sign up to set email alerts
|

Building a telepalliative care strategy in nursing homes: a qualitative study with mobile palliative care teams

Abstract: Background Despite increasing use of telemedicine in the field of palliative care, studies about the best circumstances and processes where it could replace face-to-face interaction are lacking. This study aimed to: (1) identify situations that are most amenable to the use of telemedicine for the provision of palliative care to patients in nursing homes; and (2) understand how telemedicine could best be integrated into the routine practice of mobile palliative care teams. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…This argument is premised on the basis that service provider had difficulties in conducting assessments and diagnosis via tele-consultation platforms. Similar challenges of using teleconsultation in PC service delivery has been reported in a qualitative study by Cormi et al (2021). This finding underscores the need for tertiary hospitals in Ghana to prioritize service providers' technological development through continuous professional development and implementation of emergency response strategies.…”
Section: Discussionsupporting
confidence: 78%
“…This argument is premised on the basis that service provider had difficulties in conducting assessments and diagnosis via tele-consultation platforms. Similar challenges of using teleconsultation in PC service delivery has been reported in a qualitative study by Cormi et al (2021). This finding underscores the need for tertiary hospitals in Ghana to prioritize service providers' technological development through continuous professional development and implementation of emergency response strategies.…”
Section: Discussionsupporting
confidence: 78%
“…These authors also identified technology as, essentially, a third party in the remote care equation—an additional relationship to be managed by the palliative specialist. Our study, alongside others citing high levels of patient satisfaction, suggests that certain components of this concept of telepresence come easily to palliative specialists [ 11–13 , 21 ]—such as connection, trust, being supportive, and collaboration—but that this secondary human-technological interface can be a barrier as much as it is a boon [ 7 , 22 ]. Concerns cited in earlier studies, such as potential overemphasis upon and/or neglect of symptoms [ 2 , 18 ], privacy concerns [ 23 , 24 ], injury to the patient-clinician relationship [ 25 ], and even lack of substantive benefit [ 26 ], suggest that these patient experiences were not born out of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…Telepalliative care has also been well received in the few evaluations of inpatient studies performed to date [ 13 ], despite reservations expressed by clinicians [ 21 ], particularly regarding the negative impact of remote interactions upon relationship-building. Our findings reinforce some of these misgivings while diminishing others: multiple respondents in our study cited the paradoxical dilemma of having more time for their patients while also having less access to them.…”
Section: Discussionmentioning
confidence: 99%
“…This prehospital evaluation also could be helpful to avoid overburdening of healthcare systems during a pandemic. Technologies such as telemedicine also could be helpful, specifically in cases of infectious diseases and entry restrictions in nursing homes [23][24][25]. Interestingly, the majority of referrals of COVID-19 patients to our OPC team came from general practitioners (75.0%).…”
Section: Discussionmentioning
confidence: 99%